2012
DOI: 10.1186/1756-6606-5-1
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor activation stimulates transcription-independent rapid wnt5a protein synthesis via the MAPK signaling pathway

Abstract: Wnt proteins are emerging key regulators of the plasticity and functions of adult brains. However, the mechanisms by which the expression of Wnt proteins is regulated in neurons are unclear. Using cortical primary cultures, we show here that activation of NMDA receptors (NMDARs) induces rapid Wnt5a protein synthesis and secretion. This NMDAR-regulated Wnt5a synthesis does not require transcription and is a result of activity-dependent translation. We also show that NMDAR-regulated Wnt5a translation depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 40 publications
5
70
0
Order By: Relevance
“…1G). This discrepancy is probably due to NMDAstimulated rapid translation from pre-existing mRNA, as suggested by previous studies (Ouyang et al, 1999;Li et al, 2012). Also, the ADAM10 protein increase is more transient that the increase of ADAM10 mRNA (Fig.…”
Section: Nmdar Activation Increases Adam10 Proteinmentioning
confidence: 54%
“…1G). This discrepancy is probably due to NMDAstimulated rapid translation from pre-existing mRNA, as suggested by previous studies (Ouyang et al, 1999;Li et al, 2012). Also, the ADAM10 protein increase is more transient that the increase of ADAM10 mRNA (Fig.…”
Section: Nmdar Activation Increases Adam10 Proteinmentioning
confidence: 54%
“…mRNA, messenger RNA; d, days; GSK-3b, glycogen synthase kinase 3 beta; LEF1, lymphoid enhancer-binding factor-1. by synaptic activity [54][55][56] and that the b-catenin signaling pathway played a key role in synaptic assembly, remodeling, and plasticity. [57][58][59] Moreover, our results highlight a differential pattern of expression of Fz receptors by the different cell types residing in the spinal cord, as shown for Fz1 in neurons and oligodendrocytes and Fz4 in astrocytes, suggestive for them still to unravel cellspecific patterns of Wnt receptors that might be key for the neuronglia interplay and, as a result, the modulation of neural transmission in both physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that NMDAR activation induces rapid Wnt5a protein synthesis and secretion (43). Interestingly, this NMDAR activation-stimulated Wnt5a synthesis is not dependent on transcription, and thus is a result of stimulating translation from pre-existing Wnt5a mRNA.…”
Section: Synaptic Activity-regulated Wnt Signalingmentioning
confidence: 99%